Komparasi Konsep Psikoterapi Analisis Transaksional dan Muhasabah Diri - Ali, Syahma Laudza’i Rasyidah Shofina; Nafia, Moh Fahmi Ilman (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2025)
One of the challenges faced by modern humans today relates to emotional, mental, and spiritual health. Often, a person may appear physically healthy and fit, but is actually experiencing psychological and spiritual distress. This study aims to compare Transactional Analysis and Self-Reflection, identifying similarities and differences in their objectives, processes, therapeutic techniques, and perspectives on self and soul, to support the development of a contextual psychotherapy model. The research method used in this study involves literature review and content analysis, with data collected from primary and secondary sources to analyze the main themes. The findings of this study are as follows: (1) Transactional Analysis focuses on improving communication through ego state analysis and therapeutic contracts, while Self-Reflection emphasizes spiritual reflection through tabayun and mauizah. (2) Both prioritize self-awareness but differ in their approaches. The contribution of this study enriches integrative psychotherapy and provides practical guidance for counselors rooted in religious culture.